Metabolic dysfunction-associated liver disease and biliary lithiasis in children with Down Syndrome: a retrospective study - Renato Nisihara; Nayane Hiba Fuga; Liete Maia; Marcelo Gasparin Mansur; Fernanda Liberatti; Maiana Rossasi; Nanci Oliveira (Revista Paulista de Pediatria)
ABSTRACT Objective: To investigate the presence of metabolic dysfunction-associated fatty liver disease (MAFLD) and gallbladder abnormalities in a sample of people with Down syndrome in Brazil. Methods: This is a retrospective study using medical charts involving Down syndrome patients, diagnosed by karyotype, aged over 5 years, who underwent abdominal ultrasound and were monitored by the same professional in a clinic in Curitiba, Brazil. Data spanned January 1995 to September 2023; all cases with no use of alcohol or hepatotoxic medications. Results: A total of 124 patients were evaluated, 64 (51.6%) being females. Ages varied between 5 and 30 years (average of 13.2±5.7 years). Body mass index ranged from 14.08 to 44.98 kg/m2, with 27 (21.7%) patients being overweight and 42 (33.8%) obese. The frequency of increased total cholesterol and triglyceride concentrations was significantly higher in children. No age or sex differences were seen in low- and high-density lipoprotein cholesterol. Alanine transferase (ALT) and aspartate transferase (AST) levels were within normal ranges and showed no differences concerning sex or age. Four patients (3.2%) had diagnosis of MAFLD. The prevalence of gallstone varied widely in terms of the number and size of stones among patients, affecting 11 (8.9%) of them, with no significant difference in age or sex. Conclusions: MAFLD was found in 3.2% of the individuals, while gallstone disease was identified in 8.9% of the cases studied. Moreover, we noted a significant presence of risk factors associated with MAFLD, with dyslipidemia being the predominant factor.